2021
DOI: 10.3389/fpsyg.2020.633709
|View full text |Cite
|
Sign up to set email alerts
|

The Interpersonal Mindfulness in Parenting Scale in Mothers of Children and Infants: Factor Structure and Associations With Child Internalizing Problems

Abstract: Objectives: Mindful parenting, measured by the Interpersonal Mindfulness in Parenting scale (IMP), is beneficial for parents and children. However, the IMP has not been validated in English-speaking parents. Further, little is known about whether mindful parenting is similar in parents of children vs. infants, or how it reduces child internalizing problems. We sought to validate the IMP in English-speaking mothers of children and infants, and to examine relationships between the facets of mindful parenting, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Acceptance and the theme self-compassion together reflect the IMP facet Non-judgmental Acceptance of Parental Functioning (NJAPF), which captures a parent’s ability to be accepting and compassionate regarding themself as a parent. The identification of the themes acceptance and self-compassion is consistent with evidence from earlier studies, which have found NJAPF to be the aspect of mindful parenting most predictive of child internalizing problems (Burgdorf & Szabó, 2021 ). The theme empathy encompasses the Emotional Awareness of the Child (EAC) and Compassion for the Child facets of the IMP.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Acceptance and the theme self-compassion together reflect the IMP facet Non-judgmental Acceptance of Parental Functioning (NJAPF), which captures a parent’s ability to be accepting and compassionate regarding themself as a parent. The identification of the themes acceptance and self-compassion is consistent with evidence from earlier studies, which have found NJAPF to be the aspect of mindful parenting most predictive of child internalizing problems (Burgdorf & Szabó, 2021 ). The theme empathy encompasses the Emotional Awareness of the Child (EAC) and Compassion for the Child facets of the IMP.…”
Section: Discussionsupporting
confidence: 87%
“…The theme empathy encompasses the Emotional Awareness of the Child (EAC) and Compassion for the Child facets of the IMP. After NJAPF, EAC is the only other facet of mindful parenting that has been found to predict child internalizing problems (Burgdorf & Szabó, 2021 ). Lack of awareness regarding a child’s anxiety could result in a parent failing to help the child manage that anxiety or managing it unhelpfully (Hurrell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Interpersonal Mindfulness in Parenting (IM‐P) scale, originally designed for use with adolescents (Duncan, 2007), and the Mindfulness in Parenting Questionnaire (MIPQ), intended for caregivers with children in the 2–16 years of age range (McCaffrey, 2015; McCaffrey et al, 2017), appear to be the only options. The IM‐P has been used more extensively, including studies with infants, and it should be noted most of these were conducted with international samples (Burgdorf & Szabó, 2021; Kim et al, 2019; Laurent et al, 2017; Lo et al, 2018; Moreira & Canavarro, 2017; Potharst et al, 2020). Although some of the studies including infants modified the IM‐P to make the instrument content appropriate for the younger children, these adjustment have not been uniform and often minimal in scope (e.g., “child” was changed to “baby” and “parenting” or “raising” to “nurturing”; Potharst et al, 2020).…”
Section: Introductionmentioning
confidence: 99%